SEMI-INTENSIVE SHRIMP FARMING SYSTEM OF KERALA, INDIA: A PRODUCTION FUNCTION ANALYSIS - Raju, M. S. (Journal of Indian Fisheries Association, 2015)
An analysis of the factor-product relationship in the semi-intensive shrimpfarming system of Kerala, farm basis and hectare basis, we are attemptedand the results reported in this paper. The Cobb-Douglas model, in whichthe physical relationship between input and output is estimated, and themarginal analysis then employed to evaluate the producer behaviour, wasÂ·used for the analysis. The study was based on empirical data collected duringNovember 1994 to May 1996, covering three seasons, from 21 farms spreadover Alappuzha, Ernakulam, and Kasaragod districts of the state. The samplecovered a total area of 61.06 ha. Of the 11 explanatory variables consideredin the model, the size of the farm, casual labour and chemical fertilizerswere found statistically significant. It was also observed that the factorssuch as age of pond, experience of the farmer, feed, miscellaneous costs,number of seed stocked and skilled labour contributed positively to theoutput. The estimated industry production function exhibited unitaryeconomies of scale. The estimated mean output was 3937 kglha~ The test ofmulti-co-linerity showed that there is no problem of dominant variable. Onthe basis of the marginal product and the given input-output prices, theoptimum amounts of seed, feed and casual labour were estimated. They wereabout 97139 seed, 959 kg of feed and 585 man-days of casual labour per farm.This indicated the need for reducing the stocking density and amount of feedfrom the present levels, in order to maximise profit. Based on the finding ofthe study, suggestions for improving the industry production function areproposed.Keywords : Semi-intensive shrimp farming, production function, factorproduct relationship, optimum level of input, economic of scale